2009
DOI: 10.1093/hmg/ddp076
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of bifunctional RNAs that target an intronic repressor and increase SMN levels in an animal model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a motor neuron disease caused by the loss of survival motor neuron-1 (SMN1). A nearly identical copy gene, SMN2, is present in all SMA patients, which produces low levels of functional protein. Although the SMN2 coding sequence has the potential to produce normal, full-length SMN, approximately 90% of SMN2-derived transcripts are alternatively spliced and encode a truncated protein lacking the final coding exon (exon 7). SMN2, however, is an excellent therapeutic target. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 66 publications
3
116
0
Order By: Relevance
“…In the second study, SMN levels were also increased in various sections of the spinal cord and a small positive effect on weight development and survival of the mice could be demonstrated. 126 This, so far, has been the only study that has demonstrated a therapeutic effect of an oligonucleotide in a mouse SMA model.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the second study, SMN levels were also increased in various sections of the spinal cord and a small positive effect on weight development and survival of the mice could be demonstrated. 126 This, so far, has been the only study that has demonstrated a therapeutic effect of an oligonucleotide in a mouse SMA model.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 97%
“…96 The bifunctional RNA was almost undetectable and located in intron 6 of SMN2, whereas the functional moiety was an ESE tail recruiting positive splicing factors. 126 Both of these approaches led to improved exon 7 reinclusion compared to the corresponding simple AONs lacking the functional moiety. They were also tested by intraventricular injections into the brains of SMA mice.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 99%
“…However, significant progress in the development of therapeutic strategies has been achieved. These include the following: (1) introducing the exogenous SMN1 gene by viral vectors (Foust et al, 2010;Passini et al, 2010;Valori et al, 2010;Dominguez et al, 2011); (2) increasing the SMN2 transcript and SMN protein by small-molecule drugs, such as histone deacetylase (HDAC) inhibitors (Kernochan et al, 2005;Avila et al, 2007;Garbes et al, 2009;Hauke et al, 2009); (3) transplantation of motor neuron stem cells (Corti et al, 2010); and (4) redirecting SMN2 splicing and increasing the full-length SMN2 transcript by antisense oligonucleotides (AOs) (Skordis et al, 2003;Hua et al, 2007Hua et al, , 2008Hua et al, , 2010Hua et al, , 2011Baughan et al, 2009;Williams et al, 2009;Owen et al, 2011;Passini et al, 2011;Osman et al, 2012;Porensky et al, 2012).…”
mentioning
confidence: 99%
“…8 Effectively, spinal muscular atrophy is a candidate for this therapy, with promising results on patient-derived cell lines that have been already described. [9][10][11] Moreover, many antisense oligonucleotides are already in phase II/III clinical trials, namely AVI4658 (Eteplirsen), a morpholino oligonucleotide for duchenne muscular dystrophy. 12 Classic galactosemia (MIM #230400), which affects about 1/47 000 live-births, results from deficient activity of galactose-1-phosphate uridylyltransferase (GALT, EC 2.7.7.12), an ubiquitous key enzyme in galactose metabolism, essential for nursing infants, as lactose represents their primary carbohydrate source.…”
Section: Introductionmentioning
confidence: 99%
“…8 Effectively, spinal muscular atrophy is a candidate for this therapy, with promising results on patient-derived cell lines that have been already described. [9][10][11] …”
mentioning
confidence: 99%